Virtual clinical trial simulations for a novel KRASG12C inhibitor (ASP2453) in non‐small cell lung cancer. (26th June 2021) - Sayama, Hiroyuki; Marcantonio, Diana; Nagashima, Takeyuki; Shimazaki, Masashi; Minematsu, Tsuyoshi; Apgar, Joshua F; Burke, John M.; Wille, Lucia; Nagasaka, Yasuhisa; Kirouac, Daniel C.
Abstract: KRAS is a small GTPase family protein that relays extracellular growth signals to cell nucleus. KRAS G12C mutations lead to constitutive proliferation signaling and are prevalent across human cancers. ASP2453 is a novel, highly potent, and selective inhibitor of KRAS G12C . Although preclinical data suggested impressive efficacy, it remains unclear whether ASP2453 will show more favorable clinical response compared to more advanced competitors, such as AMG 510. Here, we developed a quantitative systems pharmacology (QSP) model linking KRAS signaling to tumor growth in patients with non‐small cell lung cancer. The model was parameterized using in vitro ERK1/2 phosphorylation and in vivo xenograft data for ASP2453. Publicly disclosed clinical data for AMG 510 were used to generate a virtual population, and tumor size changes in response to ASP2453 and AMG 510 were simulated. The QSP model predicted ASP2453 exhibits greater clinical response than AMG 510, supporting potential differentiation and critical thinking for clinical trials.